Beit Alpha Cucumber: A New Greenhouse Crop for Florida - Nicole L. Shaw; Daniel J. Cantliffe (EDIS, 2009)
Revised! HS-810, a 7-page illustrated fact sheet by Nicole L. Shaw and Daniel J. Cantliffe, describes this cucumber that is similar to Dutch-type cucumbers, with shorter fruit, less susceptibility to damage, and potentially higher yields — production methods, cultivar evaluation, powdery mildew resistance, and snack-size type cultivars. Published by the UF Department of Horticultural Sciences, May 2009.